Knowledge of the perinatal care standard among women giving birth to children in the hospitals in Szczecin - Mularczyk, Agata; Stangret, Anna; Topczewska, Katarzyna; Gisicka, Kamila; Licow, Agnieszka; Ćwiek, Dorota; Sipak-Szmigiel, Olimpia (Journal of Education, Health and Sport, 2019)
Introduction: In order to improve the quality of perinatal care in Poland, the Regulation of the Minister of Health of September 20, 2012 introduced the standards of medical treatment when providing medical care from the field of perinatal care to women during the period of physiological pregnancy, physiological childbirth, postpartum and newborn care ( so-called the standards of perinatal care). Although the standards have been in force for several years, there are still problems with their compliance and their low knowledge among women giving birth.Research objective: Assessment of the level of knowledge about the Standards perinatal care and of Patients' Rights and the rights arising from them by women giving birth in the hospitals in Szczecin.Materials and Methods: The study included 335 women who have given birth in the hospitals in Szczecin. The study was performed since January 2016 till March 20158 by means of a diagnostic survey, based on the author’s questionnaire, developed on the basis of the standards of perinatal care 20th September 2012.Results: Among women giving birth vaginally 42% reported knowledge of the standard. 41% of women who have given birth by caesarean section declared that they know the standard. No statistically significant differences were found between the knowledge or lack of knowledge of the standards in terms age, education, and attend or not at antenatal class. We found statistically significant relationship between the knowledge of the standards and having a birth plan.Conclusions: 1. Knowledge of the standards declared more women, in comparison to the research conducted a few years earlier. Despite this their knowledge is still not high.2. Women in spite of declaring knowledge of the standard are not aware that they were not followed.3. There is still a need to educate women and staff on the standards of prenatal care and Patients' Rights.